Cyclic polymers with pendant triphenylene discogens: convenient synthesis and topological effect on thermotropic liquid crystal behavior and fluorescence enhancement. Issue 39 (23rd August 2016) - Mu, Bin; Li, Qian; Li, Xiao; Pan, Shi; Zhou, Yang; Fang, Jianglin; Chen, Dongzhong
Abstract : Cyclic topological constraint suppresses columnar ordering while showing remarkably enhanced fluorescence as a supplement of aggregation-induced emission (AIE). Abstract : Novel discotic liquid crystalline cyclic polymers prepared through RAFT polymerization and intrachain azide–alkyne click cyclization, exhibit fully inhibited or significantly weakened bulk columnar ordering with increased molecular weight or shortened spacer length, while exhibiting remarkably enhanced fluorescence emission in solution as a result of the cyclic topological constraint effect.